The Effect of Whole-Grain Diet on the Gut Microbiota of the Elderly Individuals - Cui, Zeying; Li, Jingtai; Zhen, Yuting; Fan, Pingming; Du, Guankui (Frontiers in Nutrition, 2022)
Whole grain diet (WGD) affects human health in multiple ways. However, the effect of WGD on the gut microbiota of the elderly is still largely unknown. WGD did not affect the microbial α-diversity, but had a profound impact on the microbes’ abundance in the elderly. WGD increased the abundance of Verrucomicrobia and decreased the abundance of Firmicutes. The prediction of microbial function showed that glucose metabolism and lipid metabolism were inhibited. In addition, the effects of WGD on the gut microbiota of normal-weight and overweight individuals were different. WGD increased Verrucomicrobia in the normal-weight group and decreased Firmicutes in the overweight group. Meanwhile, the effect of WGD on gut microbiota showed gender characteristics, Firmicutes/Bacteroidetes ratio decreased in females, while Verrucomicrobia abundance increased in males. WGD could improve the microbial composition and promote the growth of beneficial microbes, which may be beneficial to the health of the elderly